Sustainability Reporting And Assurance Statement Quality: Analysis of Reporting Practices And Standards - Wahyuni, Sri; Intan Maulida; Nasruddin; Putri, Shara Amelia (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The global issue of sustainability in business and corporate social practices has grown in importance and relevance. Sustainability reports serve as a primary communication tool for companies to inform stakeholders such as investors, consumers, government entities, and the general public about their sustainability practices. However, trust in the believability of sustainability reports is often contested, and many stakeholders doubt the information disclosed in these reports. Thus, the value of assurance in sustainable reporting has been acknowledged in order to check credibility of the data. This research used content analysis technique to review the quality of assurance statement of the assurance providers on sustainability reports of mining sector companies listed at BEI, taking into consideration the types of assurors and various standards used The findings showed that non-accounting assurors offered the highest quality of assurance when compared to its accounting counterparts. Although ISAE 3000 is more dominant as an assurance standard, it still has many limitations compared to AA1000 and GRI, as it does not focus on stakeholder inclusivity, materiality, and responsiveness, which affects the quality of assurance statements.